A study on the capability of frequency doubling perimetry in the detection of visual field abnormalities in primary open angle glaucoma patients. - Bakiah, Shaharuddin (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
Frequency Doubling Peri1netry (FDP) has become a widely used technique for both screening and follow up of glaucomatous field loss. It is thought to be sensitive and superior in the detection of early visual field loss Objective: To determine the capability ofFDP in the detection of visual field abnormalities in the primary open angle glaucoma (POAG) patients. Design: Prospective, comparative, cross sectional study. Method: 150 POAG patients underwent both FDP in screening and threshold mode 30- 2 and Humphrey Visual Field (HVF) 30-2 tests in Eye clinic Hospital Universiti Sains Malaysia (HUSM). All patients had a comprehensive ophthalmology assessment. Data analysis including sensitivity, specificity, area under the receiver operating characteristic (ROC) curve and kappa agreement between FDP and HVF was performed using SPSS system version 12.0. Results: Data from 120 POAG patients were analyzed following inclusion, exclusion criteria and reliability of the visual field testing. For FDP in screening mode, when "at least 1 missed point" \Vas used as the definition for abnormal FDP, the sensitivity was high between 92.2% to 96.2% and specificity was between 24.2% to 50.0%. When "2 or more missed points", was used as definition for abnormal visual field, the sensitivity was 89.5% to 95.0% and specificity between 33.3% to 47.0% was achieved. For FDP in threshold n1ode and HVF with various definitions for abnormal visual field, the sensitivity was between 83.5% to 100% and specificity between 0.0% to 47.0%. Kappa value for FDP and HVF was between 0.155 to 0.391 which showed poor to slight agreement. Conclusion: FDP showed high sensitivity but low specificity in the detection of visual field abnormalities among our patients. The new classification for severity of glaucoma \Vith Glaucoma Scoring System 2 (GSS2) and Frequency Doubling Technology Scoring System 2 (FDT SS2) was able to provide immediate and reliable classification for both severity and characteristic of visual field.